THE INCREASE OF BPJS CLAIMS AT HOSPITAL AFTER CHANGING TO E-MEDICAL RECORDS: CASE ANALYSIS AND MITIGATION STRATEGY - Sharah Aulia Winarsih; Bagoes Widjanarko; Farid Agushybana (Journal of Social Research, 2024)
With the advancement of digital transformation, EMR has become an important step towards operational efficiency and better care. Through Permenkes No.24 of 2022, all health facilities in Indonesia are expected to have implemented the EMR system by the end of 2023. This is a mixed-methods study that combines primary data from interviews with 5 respondents and secondary data regarding BPJS claims during the period before and after EMR implementation, from January to August 2023. Secondary data analysis will be conducted using tables, graphs, and descriptive statistics such as mean, median, and standard deviation to detail and explain changes in BPJS claims patterns before and after EMR implementation. Qualitative data will be analysed. The results showed that EMR implementation increased the number of cases (11.27%) and the nominal amount of BPJS claims (15.04%). In addition, this study identified several factors that became challenges after the change to EMR. These factors include data errors, lack of staff training, technical constraints, and changes in operational processes that have not been fully integrated with the EMR system. Mitigation strategies include staff training, periodic monitoring and evaluation, internal claim audits, improvement of claim business processes, and monitoring and evaluation from management. Based on the results of the study, it can be concluded that the change to electronic medical records (EMR) at Sultan Agung Islamic Hospital has increased starting from the number of patients, the number of cases and the nominal amount of BPJS claims. Despite the increase in the nominal amount of BPJS claims, there are still challenges and problems that need to be overcome after the implementation of EMR.